Metal-Organic Framework-Derived NiSe Embedded into a Porous Multi-Heteroatom Self-Doped Carbon Matrix as a Promising Anode for Sodium-Ion Battery - Xiaoyan Shi; Lujun Fang; Handong Peng; Xizhan Deng; Zhipeng Sun (Nanomaterials, 2022)
A self-doping strategy is applied to prepare a multi-heteroatom-doped carbonaceous nickel selenide NiSe@C composite by introducing N and P-containing ligand hexa(4-carboxyl-phenoxy)-cyclotriphosphazene (HCTP-COOH) into a Ni-based MOF precursor. The MOF-derived NiSe@C composite is characterized as NiSe particles nested in a multi-heteroatom-doped carbon matrix. The multi-heteroatom-doped NiSe@C composite with a unique structure shows an excellent sodium-ion storage property. The Na-ion battery from the NiSe@C electrode exhibits a capacity of 447.8 mA h g−1 at 0.1 A g−1, a good rate capability (240.3 mA h g−1 at 5.0 A g−1), and excellent cycling life (227.8 mAh g−1 at 5.0 A g−1 for 1200). The prospects of the synthesis methodology and application of NiSe@C in sodium-ion batteries (SIBs) devices are presented.